Cultivating imaginative thinking: teacher strategies used in high-performing arts education classrooms. Issue 4 (1st October 2016) - Fleming, Josephine; Gibson, Robyn; Anderson, Michael; Martin, Andrew J.; Sudmalis, David
Abstract : This article reports on recent case-study research that examined teacher- and student-level processes in nine Australian arts classrooms. The selected classrooms, based on the results of a connected longitudinal study, demonstrated strong positive links between arts participation and academic motivation, engagement and achievement. The focus here is on how teachers supported their students to conceive, shape and present imaginative work. Although different approaches were apparent in the dance, drama, film, music and visual arts classrooms, patterns were detected in the processes used to transform imaginative ideas into a creative work. The research indicated that important skills were being developed as the students encountered the ambiguity of the creative process. Furthermore, insights were gained into how work drawing on the imagination can be initiated and sustained through the highs and lows of development to become both a work of art and a learning experience that will augment future creative work.